(3GdeMGSHI Hjf GdfXQjI hGdJWHjb (B: s (3GdbQGAGJ GdJGQjNjI hGdEUdGMGJ heaGgje LOjOI (B/ s - (3MhGS, UdGMs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2013)
(3GdMbHI GdJGQjNjI ddeMGSHI, eGgjI GdeMGSHI, fXQjGJ GdeMGSHI, GdeMGSHI cfXGe eYdheGJ, GdbQGAI GdJGQjNjI dJWhQ GdeYGjjQ GdeMGSHjI GdOhdjI, YQV eVGejf GdeYGjjQ GdOhdjI ddeMGSHIs
(3HHdjhZQGajG(B: (3U(B.182s
Keywords: (3GdeMGSHIs; (3GdeMGSHI GdOhdjIs